Deep Neck Infection Associated with Peritoneal Sepsis A Rare Death Case - Özsoy, Sait; Gökmen, Asude; Yöndem, Mehtap; Sücüllü, İlker and Duran, Semra and Javan, Gulnaz Tatlıcı (The Bulletin of Legal Medicine, 2016)
Deep neck infection often develops due to upper respiratory tract and odontogenic infections. Gastrointestinal System perforation can occur for many reasons and is in need of early diagnosis and prompt suigical treatment. In both cases late or incorrect diagnosis may lead to increased morbidity and high mortality An inmate suffering from a deep neck infection which developed from a tooth abscess and resulted in multiple organ failure and septic shock died while being treated in a hospital. The autopsy confirmed “retropharyngeal abscess” and revealed in addition findings of duodenal perforation that was missed during clinical examination. According to Turkish Criminal Code, a finding of a misdiagnosis should not just be reported as the cause of death but clearly stated in the report. Keywords: Dental focal infection; Retropharyngeal Abscess; Peptic Ulcer perforation; Peritonitis; Sepsis; Autopsy